(untitled) (Escuela Abierta, 2019)
The text is devoted to analysis of mental qualities of: a) children starting their education at primary school, b) children attending the following years at the stage of integrated education. The author emphasizes that qualities typical for both groups refer to qualitatively different levels of human's mental development.Six-year-olds and younger ones are characterized by: pictorial and pre-operational thinking, high level of excitement, low level of emotioncontrol, realism, moral heteronomy and ability to participate in simultaneous or group games.The older ones develop gradually: realistic and operational thinking, competences related to conventionality and moral relativism, ability toparticipate in group games, independent and responsible response to didactic tasks given by a teacher to the whole class, as well.According to the author, psychological knowledge on differences between mental qualities of both groups mentioned above, have beenonly partially exploited in pedagogy.Aims, content and methods of educational activity in their various phases of integrated education should be different not only in terms of quality but also in terms of quantity.